Influence of functionalities over polymer, trimer, dimer formation and optical properties of cadmium dithiocarbamates. (15th October 2016) - Manar, Krishna K.; Yadav, Manoj K.; Anamika,; Drew, Michael G.B.; Singh, Nanhai
Graphical abstract: Homoleptic cadmium(II) bis(dithiocarbamate) complexes displaying 1D coordination polymeric (1 –3 ), trimeric (4 ) and dimeric (5 ) structures have been synthesized and fully characterized. Their luminescent properties have been studied. Abstract: Homoleptic cadmium(II) bis(dithiocarbamate) complexes having polymeric [Cd(L)2 ]∞ (L = C7 H5 O2 CH2 NCS2 CH2 C6 H5 (L1), 1 ; C6 H4 NO2 CH2 NCS2 CH2 C4 H3 O (L2), 2 ; C6 H4 FCH2 NCS2 CH2 C4 H3 O (L3), 3 ), trinuclear [Cd(L4)2 ]3 (L4 = 4-ClC6 H4 CH2 NCS2 CH2 C4 H3 O, 4 ) and dinuclear [Cd(L5)2 ]2, (L5 = 3-ClC6 H4 CH2 NCS2 CH2 C6 H5, 5 ) structures have been synthesized and characterized by elemental analyses, spectroscopy (IR, 1 H and 13 C 1 H NMR and UV–Vis.) and their structures have been revealed by X-ray crystallography. In1 –3 the dithiocarbamate ligands are uniquely bonded to the Cd atoms in a μ2, κ 2 S, S-chelating-bridging fashion, portraying 1D coordination polymeric structures in which the cadmium(II) ions adopt six coordinate distorted octahedral structures. In4 the six dithiocarbamate ligands are spectacularly arranged about the Cd atoms resulting in a centrosymmetric trinuclear complex in which the central metal adopts an octahedral geometry and the terminal Cd atoms are in square pyramidal environments. Complex5 has the well-established centrosymmetric dimeric structure in which the metal atoms have a five-coordinate trigonal bipyramidal geometry. Complexes1 –4 are rare examples of polymeric and trinuclear cadmium dithiocarbamate complexes.1 –5 show luminescent characteristics in solution and in the solid state arising from the metal perturbed intra-ligand charge transfer (ILCT) states. Their TG analyses show a single step decomposition with the formation of CdS nanoparticles, which have been examined by PXRD and HRTEM.